The three hurdles of tax planning: How business context, aims of tax planning, and tax manager power affect tax - Anna Feller; Deborah Schanz (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
The question of why some companies pay more taxes than others is a widely investigated topic of interest. One of the famous suspect explanations is a phenomenon called tax avoidance. We develop a holistic theoretical concept of influences on corporate tax planning through a series of 19 in-depth German tax expert interviews. Our findings show that three distinct hurdles in the tax planning process can explain different levels of tax expense across companies. Those three hurdles are which tax planning methods are. available (defined by business context), desirable (given via aims of tax planning), and implementable (determined by tax manager power). A large part of previous research has estimated the influence of firm characteristics, which we define as part of the business context, on the tax expense, while the other influences that we identify have largely been left "out of the equation". In order to apply and operationalize the identified three-hurdle concept, we construct five short, real-world company case studies. In these case studies, we show how variation in two key constructs across companies leads to different levels of tax expense. First, companies vary widely in the aggressiveness of their aims of tax planning. Second, tax managers can assume very different levels of power in their organization, determining the ability to implement tax planning methods. In conclusion, we provide generalizable insights into the tax planning process of companies which help to explain the observed variation in tax expenses across firms.
Keywords: D22; H25; M12; M41; 330; tax planning; tax avoidance; manager power; qualitative research